Occupational Competence of Specifications Coastal Tour - Guide Based on the Functional Analysis Framework - Natthanitcha Singburaudom ณัฏฐณิชชา สิงห์บุระอุดม; Varataya Thammakittipob วรัทยา ธรรมกิตติภพ; เข็มทอง พนิต (Dusit Thani College Journal, 2018)
Due to the occupational competence is a manifestation of the professional characteristics for those who want to pursue a career. Strive and train themselves to be a knowledgeable person. Proficiency in the profession represented by the occupational competencies. Therefore, the purpose of this research is to study the characteristics and occupational competencies of specifications coastal tour guides based on the functional analysis framework. Using descriptive research methods. The target population in the research were 30 of coastal tour guides and tourism scholars. The tools used to collect data were the conference record form. And gather data by means of group meetings for consensus. Analyze data using content analysis then group data and summarize the topics. The results of the study found that: 1) Desirable Characteristics of coastal tour guides consisted of: 1. Good Educator, 2. Good Planner and Coordinator, 3. Good Entertainment Enthusiast, 4. Good Communicator, 5. Good Facilitator, and 6. Good group leader. 2) The occupational competence of coastal tour guides summary into 10 key roles which including of 1) Planning a coastal tour, 2) Pick up and drop at the appointment point, 3) Communicate for coastal tours, 4) Carry out coastal tourism activities, 5) Export tourists, 6) Coastal Tourism Safety Planning, 7) Help coastal tourists to secure both life and property, 8) Analysis of assistance needs or special requests of tourists, 9) Make a report on coastal marine tours, and 10) Make an evaluation report on the performance of coastal tours.